Interpreting “Held by the State”: Article 38 (1) Copyright Law and Traditional Cultural Expression Protection - Amrulla, Mohammad Fahrial; Kusumadara, Afifah; Santoso, Budi; Widyanti, Yenny Eta (Rechtsidee, 2026)
General Background Traditional cultural expressions constitute communal cultural heritage embodying identity, philosophy, and collective memory, requiring legal protection aligned with their communal and sacred nature. Specific Background In Indonesia, traditional batik motifs—particularly the sacred Parang motifs of the Yogyakarta Sultanate—are classified as traditional cultural expressions whose copyright is declared “held by the state” under Article 38 paragraph (1) of Law No. 28 of 2014 on Copyright. Knowledge Gap This formulation contains normative ambiguity, as it does not clearly define whether state authority represents ownership, public trusteeship, or mere administrative control, resulting in weak legal certainty for indigenous custodians. Aims This study examines the legal meaning of the phrase “held by the state” in relation to the protection of sacred Parang batik motifs within the framework of traditional cultural expressions. Results The analysis shows that the provision functions as a declarative norm lacking substantive mechanisms, failing to recognize customary authority, community consent, or benefit-sharing, and thereby permitting desacralization and misuse of sacred motifs. Novelty This research clarifies that state control over traditional cultural expressions should be interpreted as public trusteeship rather than ownership, drawing comparative insights from community-centered protection models in India and Thailand. Implications The findings support the development of a sui generis legal framework integrating customary law, community participation, and administrative facilitation to ensure sustainable and culturally respectful protection of sacred batik motifs. Highlights: Article 38 paragraph (1) operates as a declarative norm without concrete protective mechanisms Legal ambiguity weakens recognition of indigenous custodianship over sacred motifs Comparative models support community-based rights with state administrative roles Keywords: Batik, Traditional Cultural Expression, Copyright, State Held